Efecto del Programa de Ejercicios con las Figuras M3 sobre la Coordinación (Effect of the Exercise Program with Figures M3 on Coordination) - Montenegro Arjona, Oscar Alfredo; Morales Vargas, Milton Mauricio; Parra Buendía, Jorge Mario (Retos, 2021)
El propósito del estudio fue analizar el efecto de la intervención del programa de ejercicios coordinativos de equilibrio, reacción y diferenciación para fútbol, con las figuras M3, sobre el desarrollo de la coordinación motriz. Se realizó un diseño experimental con pretest, postest y grupo control. Participaron 25 niños de la escuela de fútbol Coofisam de Tarqui, Colombia. El grupo experimental fueron 13 niños (edad 12.57 años ± 0.72, talla 1.50 m ± 0.06, masa corporal 44.30 kg ± 9.65, IMC 20.32 ± 3.64) y el grupo control fueron 12 niños (edad 12.58 años ± 0.63, talla 1.48 m ± 0.08, masa corporal 45.85 kg ± 10.92, IMC 20.44 ± 280). El programa de ejercicios con las figuras M3 para fútbol fue de ocho semanas, 267 ejercicios, tres sesiones por semana e intensidad vigorosa. La coordinación motriz se midió con la prueba The KörperkoordinationsTest für Kinder. Se aplicó ANOVA factorial de diseño mixto. Los resultados indican interacción significativa de los factores tipo de intervención por grupo (p < .05). No se encontró efecto principal significativo del factor grupo (p > .05) y se encontró efecto principal significativo del factor tipo de intervención (p < .05). El efecto del programa de ejercicios para fútbol, con las figuras M3, fue positivo en el desarrollo de la coordinación motriz en los jugadores de la escuela de fútbol, lo cual sugiere que la práctica de ejercicios orientados a la mejora de las capacidades coordinativas de equilibrio, reacción y diferenciación produce mejoras en la coordinación motriz. Abstract. The purpose of the study was to analyze the effect intervention of the coordination exercise program of balance, reaction, and differentiation for soccer, with the M3 figures, on the development of motor coordination. An experimental design was performed with pretest, posttest, and control group. 25 children from the Coofisam soccer school in Tarqui, Colombia participated. The experimental group was 13 children (age 12.57 years ± 0.72, height 1.50 m ± 0.06, body mass 44.30 kg ± 9.65, BMI 20.32 ± 3.64) and the control group was 12 children (age 12.58 years ± 0.63, height 1.48 m ± 0.08, body mass 45.85 kg ± 10.92, BMI 20.44 ± 280). The exercise program with the M3 figures for soccer was eight weeks, 267 exercises, three sessions per week, and vigorous intensity. Motor coordination was measured with The KörperkoordinationsTest für Kinder. Mixed design factorial ANOVA was applied. The results indicate a significant interaction of the type of intervention per group factors (p < .05). No significant main effect of the group factor was found (p > .05) and a significant main effect of the type of intervention factor was found (p <.05). The effect of the soccer exercise program, with the M3 figures, was positive in the development of motor coordination in the soccer school players, which suggests that the practice of exercises aimed at improving coordination abilities of balance, reaction, and differentiation produces improvements in motor coordination.